A copper nanoparticle enhanced phase change material with high thermal conductivity and latent heat for battery thermal management. (August 2022) - Ma, Chuyuan; Zhang, Ying; Hu, Sihang; Liu, Xiaojie; He, Song
Abstract: In order to maintain the safety temperature of power battery pack within electric vehicle, an anti-leakage composite phase change materials (CPCM) of paraffin (PA)/expanded graphite (EG)/copper nanoparticle (CN) with enhanced thermal conductivity was proposed. Its thermal properties and heat dissipation were verified by thermal property test and discharge experiment respectively. The results show that PA/EG/CN can well control the temperature of the battery pack within a safe range. The CPCM-based battery module shows excellent heat dissipation, the maximum temperature ( T max ) decrease 2.6 °C and 7.2 °C during 1 C and 2 C discharge tests. The temperature difference is 1.0 °C and 0.8 °C. The cooling effect is better under high-rate discharge. During multiple discharge-charge cycle, we find that although the latent heat of the CPCM is limited, the latent heat of the CPCM can be effectively recovered for the abeyance time, which proposes a guiding strategy for the design of CPCM battery thermal management system. Highlights: A new composite phase change materials(CPCM) is successfully prepared. Thermal and physical properties of the CPCM are experimentally measured. CPCM enhances the heat transfer for battery management system. The abeyance time can recover the latent heat of the CPCM.